The ultimate HTML reference - Lloyd, Ian (Australia : Sitepoint, 2008)
A comprehensive, authoritative, and completely up-to-date. The book covers: Every element in the HTML and XHTML Specifications, including an example of its correct use Coverage of depreciated elements and those from the upcoming HTML 5 specification.
Keywords: HTML editors (Computer programs).